Navigating Identity and Exile: Exploring Themes of Diaspora, Alienation, and Dislocation in Contemporary Indian Literature - Majid, Waseem (International Journal of Psychosocial Rehabilitation, 2019)
The research paper delves into the intricate realm of diaspora, focusing on its portrayal and exploration within contemporary Indian literature. Drawing insights from a wide range of literary works, the study analyses the multifaceted themes of alienation, dislocation, and identity crisis faced by individuals navigating the intricate terrain of migration. The paper examines how Indian authors, including Salman Rushdie, Jhumpa Lahiri, Bharti Mukherjee, and others, articulate the experiences of those living in foreign lands, juxtaposing their original homeland with the adopted one. The term "diaspora" is investigated through a historical lens, tracing its origins and evolution from the dispersion of the Jews to the modern-day global movements. The paper scrutinizes the divergent trajectories of diasporic experiences, highlighting the various motivations behind migration, such as economic prospects, religious propagation, and political upheaval. By scrutinizing representative works, the study dissects the intricate layers of identity crisis faced by protagonists who oscillate between multiple cultural influences, often leading to a struggle to define their sense of self. The texts reveal how diaspora literature captures the complex interplay between the yearning for a lost homeland and the challenges of integration into new societies. Through a comprehensive examination of key literary works, the research unpacks the thematic threads that bind these narratives together, emphasizing the commonalities and contrasts in the portrayal of diasporic experiences. Furthermore, it underscores the pivotal role of literature in not only reflecting the multifarious realities of migration but also in advocating for social justice, equality, and cultural understanding. The exploration encompasses genres beyond the traditional novel and extends to poetry, drama, autobiography, memoirs, and travelogues, illustrating the depth and breadth of the diaspora discourse within Indian literature. Ultimately, the paper contributes to a deeper understanding of how contemporary Indian writers grapple with the complexities of identity, dislocation, and the ever-evolving notion of home in an interconnected world.